Symbolic Meaning of Images of Moon and Month in Poetry of Li Bo and Sergei Yesenin - C. Wang; K. N. Galay (Научный диалог, 2025)
The article is dedicated to the study of the symbolism of the images of the Moon and the Month in the works of the Chinese poet Li Bo and the Russian poet Sergey Yesenin, as well as to defining the cultural and aesthetic significance of these concepts in the individual-authorial perception of both poets. The authors of the article argue that in Yesenin’s poetry, the image of the Month is created based on a synthesis of folk traditions and Christian beliefs, with the Moon and the Month serving as symbols associated with events from the past, nostalgia, and a sense of the irreversibility of time, as well as harbingers of the poet’s impending demise. It is demonstrated that in Li Bo’s poetry, the Moon symbolizes various phenomena of human life: noble character, life ideals, longing for relatives and friends, as well as the historical and political peculiarities of the country. The article shows that in the works of both poets, the images of the Moon and the Month are connected to the theme of their native land, the motif of solitude, appreciation of female beauty, and engagement with “eternal” questions of existence. Through comparative analysis, the article reveals the distinctive influences of cultural and historical factors on the interpretation of the images of the Moon and the Month in the poetry of Li Bo and Yesenin. This article contributes to understanding the symbolic language and metaphorical interpretation of images in the works of Chinese and Russian poets, as well as the cultural and philosophical traditions that shaped their worldview.